A Christmas story - Clark, Bob, 1941-2007; Dillon, Melinda, 1939-2023; McGavin, Darren, 1922-2006; Billingsley, Peter; Shepherd, Jean. (Burbank, CA : Warner Home Video, 2007)
In Depression-era Indiana, nine-year-old Ralphie wishes for a Red Ryder BB-gun for Christmas over his parents' objections.
Based on the novel "In God we trust, all others pay cash" by Jean Shepherd.
Features: theatrical trailer.
Melinda Dillon, Darren McGavin, Peter Billingsley.
MPAA rating: PG.
DVD, Dolby digital mono.
In English, French, or Spanish with optional English, French, or Spanish subtitles.
Keywords: Shepherd, Jean -- Film and video adaptations; Christmas plays; Boys -- Drama; Families -- Drama; Video recordings for the hearing impaired; Fiction films; Based on the book; Feature films; Christmas films; Comedy films